Prospective Study of the Mental Health Consequences of Sexual Violence Among Women Living With HIV in Rural Uganda - Tsai, Alexander C.; Wolfe, William R.; Kumbakumba, Elias; Kawuma, Annet; Hunt, Peter W.; Martin, Jeffrey N.; Bangsberg, David R.; Weiser, Sheri D. (Journal of interpersonal violence, 2016)
The association between sexual violence and depression is well known, but the temporal aspects of the association have not been well established. We analyzed data from a cohort of 173 HIV-positive women in rural Uganda who were interviewed every 3 months for a median of 1.8 years of follow-up. The method of generalized estimating equations (GEE) was used to model the marginal expectation of depression symptom severity (Hopkins Symptom Checklist for Depression), mental health–related quality of life (MOS-HIV Mental Health Summary), and heavy drinking (Alcohol Use Disorders Identification Test) as a function of self-reported forced-sex victimization in the 3 months prior to interview.
Keywords: HIV; Domestic violence; Rape; Uganda; Depressive disorder